El 71 : anatomía de una crisis - Fornet, Jorge, 1963- (Historia y Ciencias Sociales Ser., 2022)
"There are years that pass and leave no trace; others, on the other hand, seem destined to indelibly mark the historical and cultural memory. The year 1971 is one of those dates in which history seems to thicken and the writings, acts and gestures are inscribed in paradigmatic configurations, since seldom events that occurred in Cuba had such an international repercussion. Appealing to a vast repertoire of sources, from publications of the period to memoirs, letters and recent studies, the author has vividly reconstructed for us the chronicle of a year (and, with it, of a time shaken, above all, by the so-called case Padilla) memorable in events and consequences. A painstaking investigative work supports this book, which, however, can be read at once, like a novel, and which has the merit of being an exhaustive study and at the same time leaving open a space that invites debate"--